2002
DOI: 10.4049/jimmunol.169.8.4354
|View full text |Cite
|
Sign up to set email alerts
|

Stromal Cells Provide the Matrix for Migration of Early Lymphoid Progenitors Through the Thymic Cortex

Abstract: During steady state lymphopoiesis in the postnatal thymus, migration of precursors outward from the deep cortex toward the capsule is required for normal differentiation. Such migration requires, at a minimum, expression of adhesive receptors on the migrating lymphoid cells, as well as a stable matrix of their ligands persisting throughout the region of migration. In this study, we address the nature of this adhesive matrix. Although some precursor stages bound efficiently to extracellular matrix ligands, a sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
53
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(57 citation statements)
references
References 45 publications
4
53
0
Order By: Relevance
“…Because thymocyte development is tightly controlled by the size of the thymic stromal niche, improved TEC regeneration may increase the stromal scaffold available to support development and export of newly derived T cells. 10,11,29,47 Data from several reports support the notion that thymocytes supply "crosstalk" signals to support TEC development in both mice and humans. [48][49][50][51][52][53] This idea may also hold true for TEC regeneration after depletive regimens.…”
Section: Discussionmentioning
confidence: 52%
“…Because thymocyte development is tightly controlled by the size of the thymic stromal niche, improved TEC regeneration may increase the stromal scaffold available to support development and export of newly derived T cells. 10,11,29,47 Data from several reports support the notion that thymocytes supply "crosstalk" signals to support TEC development in both mice and humans. [48][49][50][51][52][53] This idea may also hold true for TEC regeneration after depletive regimens.…”
Section: Discussionmentioning
confidence: 52%
“…10 Stromal cells are generally believed to be responsible for establishing the thymic microenvironment, and consequently, for inducing the steady state production of mature T lymphocytes from uncommitted Table 1 The Letters to the Editor progenitors thus revealing important principles about the lymphoid differentiation process. 11 In our study, an aberrant HLA-DR expression on BM-derived MSCs was documented in some LPD, thus suggesting unreported possible interactions between BM stromal cells and early lymphoid progenitor cells. Furthermore, because cytokines treatment (IL-1b, INF-y and TGF-b) was reported to modulate the expression of antigenpresenting molecules on cultured human fibroblasts and epithelial cells, 12 in this study, we gave evidence that HLA-DR expression on MSCs was also found to be related to different culture conditions, 13 as it was more expressed under angiogenic conditions.…”
mentioning
confidence: 81%
“…We also found both of these to be expressed by thymic stromal cells. We and others have previously found VCAM-1 expression by thymic stroma (Salomon et al, 1997;Prockop et al, 2002), and we have shown it to be a critical ligand for transcortical migration of intrathymic progenitors (Prockop et al, 2002). Likewise, ICAM-1 has been shown by others to be expressed on various thymocytes, including thymocytes themselves (Reiss and Engelhardt, 1999), nurse cells (Cordes et al, 1997;Oliveira-dos-Santos et al, 1997), and other stromal cells (Reiss and Engelhardt, 1999;Lucas and Germain, 2000).…”
Section: Discussionmentioning
confidence: 99%